2019
DOI: 10.22578/ijms.17.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of TTV Antigen in Patients With Hepatitis HBV and HCV

Abstract: Background: Several lines of evidence have suggested the presence of new hepatitis agents, in addition to established hepatitis viruses A-E. Torque Teno virus (TTV) was more prevalent in patients with hepatitis, so it was thought to have hepatotropic properties. Objective: To detect TTV Ag in apparently healthy blood donors and patients infected with chronic hepatitis B virus (HBV) or chronic hepatitis C virus (HCV) by enzyme linked immunosorbent assay (ELISA) technique. Also, to find out any possible associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…The present study indicated that 81% of hemodialysis patients tested positive for TTV DNA for UTR region as illustrated in the figure (1). While only 1 out of 100 (1%) samples was positive for ORF-1 region as shown in the figure (2).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The present study indicated that 81% of hemodialysis patients tested positive for TTV DNA for UTR region as illustrated in the figure (1). While only 1 out of 100 (1%) samples was positive for ORF-1 region as shown in the figure (2).…”
Section: Resultsmentioning
confidence: 91%
“…Also, this study is close to what's mentioned by Magu et al who detected TTV DNA in 77% of HCV patients (42) . Furthermore, in Iraq, TTV-Ag was detected in 89 of the HBVpositive patients and in 30.8% of the HCVpositive patients (2) . The current data disagree with Chattopadhyay et al who showed that among TTV-positive patients, HCV co-infection was absent (17) .…”
Section: Phylogenetic Treementioning
confidence: 96%
See 2 more Smart Citations
“…First discovered in a serum samples from Hepatitis B (HBV) and Hepatitis C (HCV) patients ( Khudair et al, 2019 ), TTV are single-stranded circular DNA (ssDNA) viruses, with a ~ 3.8 kb genome size and are currently classified into the Anelloviridae family under the genus Alphatorquevirus ( Lolomadze and Rebrikov, 2020 ). TTV are known to be a diverse viral group with over 20 genotypes and 40% viral genome heterogeneity with frequent recombination in the N22 region of the open reading frame (ORF) 1 gene ( Manni et al, 2002 ; Hino and Miyata, 2007 ; Hsiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%